PENERAPAN STANDAR OPERASIONAL PROSEDUR FORKLIFT DI PT. X KABUPATEN PADANG PARIAMAN - Herlina, Yeni; Murdina Asih, Wenny (Ensiklopedia of Journal, 2023)
PT. X. is a company engaged in the manufacturing of iron, steel and concrete which in its work process uses a forklift as one of the lifting equipment. This certainly has the potential to cause work accidents and occupational diseases. PT. X Padang Pariaman Regency has forklift SOPs as an effort to prevent work accidents. The purpose of this research is to apply the application of standard forklift operational procedures at PT. X District of Padang Pariaman. This research design is descriptive qualitative. Data obtained by conducting observations, interviews and company documents. Interviews were conducted with 2 informants, namely the HSE Secretary and the Forklift Operator at PT. X District of Padang Pariaman. The results of the interviews were processed by carrying out data reduction, data display, and data verification. Data analysis Refer to the forklift safety quickcard (OSHA 3949 – 2019). The results of this study indicate that the policies and work processes at PT. X Padang Pariaman Regency has been implemented, but not all OSHA 3949 - 2019 items are included in the work instructions at PT. X District of Padang Pariaman.Keywords: Application of SOP, Forklift, Safe Forklift Operation OSHA (2019)